Analisis Tingkat Efektivitas Dan Efisiensi Pengelolaan Keuangan Dalam Mengevaluasi Kinerja Keuangan Sekolah Menegah Pertama Islam Terpadu Kahar Rahman - Husna fitria; Basir, Indra (Universitas Sulawesi Barat, 2023)
Financial management is an activity that includes financial procurement, use of finance and financial responsibility in achieving educational goals efficiently and effectively. Assessing financial management performance is something that has an impact on schools to see whether their performance is running and being managed well and correctly. The aim of this research was to assist schools in analyzing the level of effectiveness and efficiency of financial management in improving financial performance at SMP IT Kahar Rahman using the effectiveness ratio, financial ratio and efficiency ratio methods. The data used is qualitative data with a descriptive approach, a case study at SMP IT Kahar Rahman, Rengat sub-district. Data collection is primary by conducting interviews obtained directly from the treasurer. The results of this research show that the level of efficiency of financial management at SMP IT Kahar Rahman has been carried out quite well and effectively, then the level of efficiency of financial management in calculating financial ratios shows that the school is less able to utilize its assets and in calculating efficiency ratios it shows that the school is good and very efficient in utilize resources for financial management.